Antioxidant And Antibacterial Activity Of Methanolic Extract Of Machilus Odoratissima - Subedi, Amit; Amatya, Mohan Prasad; Shrestha, Tirtha Maiya; Mishra, Shyam Kumar; Pokhrel, Bharat Mani (Kathmandu University Journal of Science, Engineering and Technology, 2012)
The methanol extract of the bark of Machilus odoratissima was subjected to investigate its antioxidant and antibacterial properties. The phytochemical screening demonstrated the presence of different types of compound like terpenoids, tannins, deoxy sugar, saponins and phenolic compounds. The methanol extract of the plant was tested for antioxidant activity using scavenging activity of DPPH(1,1-diphenyl-2-picrylhydrazil) radical method and antibacterial activity against Staphylococcus aureus, Enterococcus faecalis, Escherichia coli & Pseudomonas aeruginosa bacteria using cup plate method. The extract exhibited high free radical scavenging activity. IC50 was found to be 3.37μg/ml. Antibacterial activity was observed against S. aureus in dose dependent manner DOI: http://dx.doi.org/10.3126/kuset.v8i1.6045 KUSET 2012; 8(1): 73-80